Dakwah Berbasis Iklan Layanan Masyarakat 3M di Masa Pandemi Covid-19 - Ahmad Hidayatullah; Luluk Azizah (KOMUNIDA : Media Komunikasi dan Dakwah, 2022)
The Covid-19 pandemic has forced everyone to adapt to new patterns. One of them is in the world of communication as experienced by PPK FM Sragi Community Radio. The radio, which operates based on an educational and da'wah mission, must innovate more adaptively in order to keep listeners from enjoying its broadcast programs. Using this type of qualitative research and descriptive analysis, this study tries to explore how da'wah based on 3M public service advertisements during the Covid-19 Pandemic was carried out by PPK FM Community Radio Sragi Pekalongan in 2020. As for the results of this study, it can be concluded that da'wah based on public service advertisements about 3M on PPK FM Sragi Community Radio was carried out as an effort to raise public awareness of the importance of implementing health protocols during the Covid-19 Pandemic. This is important considering that maintaining health and personal safety is also part of maqashidus shari'ah, namely hifdzun nafs (keeping the soul).